Role of Kangaroo Mother Care in Growth and Breast Feeding Rates in Very Low Birth Weight (VLBW) Neonates - Saeed Nazir, Aqsa Mubashar, Bilquis Naeem, Maira Riaz, Lubna Aman, Nayla Salman, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: World Health Organization has recommended kangaroo mother care for every infant weighing less than 2,000gs who is stable. The Kangaroo mother care (KMC) has been established for last few decades because there are insufficient resources in developing countries to care for infants with low birth weights (LBW). Methodology: It is a non-controlled retrospective observational cohort. Results: If we compare the means of the weights and lengths at birth, one month and three months there is statistically significant improvement in both groups. The growth at three months is better in KMC group. The mean of the day of breastfeeding and the KCM intervention are positively associated. The initiation of breastfeeding is different in both groups. Practical Implications: The intervention has long term benefits as the results have shown better association of KMC at three months. Early initiation and high rate of breastfeeding in KMC group also suggests positive association. Conclusion: Kangaroo mother care can be implemented as it shows positive outcomes. Keywords: Kangaroo Mother Care, Kangaroo mother method, Exclusive breastfeeding, neonatal care, Low birth weight.